2011
DOI: 10.1021/mp2001704
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem (iPS) Cells Repair and Regenerate Infarcted Myocardium

Abstract: Cardiac myocyte differentiation reported thus far is from iPS cells generated from mouse and human fibroblasts. However, there is no article on the generation of iPS cells from cardiac ventricular specific cell types such as H9c2 cells. Therefore, whether transduced H9c2 cells, originally isolated from embryonic cardiac ventricular tissue, will be able to generate iPS cells and have the potential to repair and regenerate infarcted myocardium remains completely elusive. We transduced H9c2 cells with four stemne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 30 publications
5
69
0
Order By: Relevance
“…uman induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are used for developing cardiac therapies, [1][2][3][4][5][6][7] modeling cardiac development or disease, [7][8][9][10][11] and screening new drugs for efficacy or cardiotoxicity. 8,9,12,13 By studying hiPSC-CMs in engineered heart tissues, which are three-dimensional tissue constructs comprised of cardiomyocytes in a hydrogel, hiPSC-CMs show a more mature phenotype than two-dimensional cultured cardiomyocytes.…”
mentioning
confidence: 99%
“…uman induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are used for developing cardiac therapies, [1][2][3][4][5][6][7] modeling cardiac development or disease, [7][8][9][10][11] and screening new drugs for efficacy or cardiotoxicity. 8,9,12,13 By studying hiPSC-CMs in engineered heart tissues, which are three-dimensional tissue constructs comprised of cardiomyocytes in a hydrogel, hiPSC-CMs show a more mature phenotype than two-dimensional cultured cardiomyocytes.…”
mentioning
confidence: 99%
“…These cells were then differentiated into cardiomyocytes. This study showed that regeneration of heart tissue after a myocardial infarction was possible using cardiomyocytes differentiated from iPSC (18).…”
Section: Escsmentioning
confidence: 88%
“…Fibroblasts and adipose tissue are commonly used to create iPSCs; however, somatic cells can be taken from anywhere in the body. Singla et al (18) showed the first successful transformation of H9C2 cells, also known as cardiomyoblasts, into iPSCs using the transcription factors mentioned previously. These cells were then differentiated into cardiomyocytes.…”
Section: Escsmentioning
confidence: 99%
“…Our strategies to limit teratoma formation could have been augmented with updated differentiation protocols that yield a greater percentage of cardiac-lineage specification. Previous studies have shown that while intramyocardial transplantation of undifferentiated rat iPSCs resulted in tumorigenesis in the heart [33], terminally differentiated iPSC-derived human cardiomyocytes have significantly improved cardiac function after ischemic cardiomyopathy [33,34]. Additionally, embryonic stem cells have been differentiated to cardiomyocytes and transplanted to form stable intracardiac grafts [35], providing evidence for similar cardiac repair with iPSC-based therapy.…”
Section: Discussionmentioning
confidence: 99%